2000
DOI: 10.1104/pp.124.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific and Developmental Pattern of Expression of the Rice sps1 Gene

Abstract: Sucrose-phosphate synthase (SPS) is one of the key regulatory enzymes in carbon assimilation and partitioning in plants. SPS plays a central role in the production of sucrose in photosynthetic cells and in the conversion of starch or fatty acids into sucrose in germinating seeds. To explore the mechanisms that regulate the tissue-specific and developmental distribution of SPS, the expression pattern of rice (Oryza sativa) sps1 (GenBank accession no. U33175) was examined by in situ reverse transcriptase-polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 82 publications
3
34
0
Order By: Relevance
“…Sucrose is synthesized in the scutellum by sucrose phosphate synthase (Nomura et al, 1969;Chávez-Bárcenas et al, 2000) and transported to the embryo and coleoptile through the phloem. The activity of sucrose synthesis in the scutellum and the sucrose loading to the phloem may affect sucrose content of the shoot.…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose is synthesized in the scutellum by sucrose phosphate synthase (Nomura et al, 1969;Chávez-Bárcenas et al, 2000) and transported to the embryo and coleoptile through the phloem. The activity of sucrose synthesis in the scutellum and the sucrose loading to the phloem may affect sucrose content of the shoot.…”
Section: Discussionmentioning
confidence: 99%
“…5C). It was reported that sps1 (a gene encoding sucrose phosphate synthase) expression shows transversal gradient in sheathed leaves, being higher in the outermost and lower in the innermost (Chávez-Bárcenas et al, 2000). These authors suggested that light, in part, has a major infl uence on the pattern of sps1 expression during leaf development.…”
Section: Discussionmentioning
confidence: 99%
“…Because clear induction of the genes for α-amylase3D and SPS was reported in germinating seeds (Chavez-Barcenas et al 2000, Nanjo et al 2004, we considered them as representative genes being expressed when/where starch degradation and sucrose biosynthesis occurred. However, both genes showed unexpected expression patterns in the leaf sheaths of the first leaves below the flag leaves ( Fig.…”
Section: Discussionmentioning
confidence: 99%